Gamma-ray irradiation effects on dynamic gain of erbium-doped fiber amplifiers - Jou, Jau-Ji; Liu, Cheng-Kuang; Lai, Fu-Shun (Oficyna Wydawnicza Politechniki Wrocławskiej, 2010)
Experiments were made of the gamma-ray irradiation effect on the dynamic performance of erbium-doped fiber amplifiers (EDFAs). The frequency responses of EDFAs before and after irradiation are dependent on radiation dose and modulation frequency. The ac gain of EDFA with irradiation effect was also simulated, and our simulations are in agreement with the experimental results.
Optica Applicata, Vol. 40, 2010, nr 4, s. 921-926
Keywords: optyka; erbium-doped fiber amplifier; gamma-ray irradiation